Grain Sorghum Cost-Return Budget (W-S-F Rotation) in Western Kansas - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1998)
This publication projects a budget that reflects expected income and costs based on typical production of grain sorghum in western Kansas.
MF904_1998_10
Keywords: MF904; Economics; Crops; MF